Calcification in Salivary Gland Cancer Mimicking Sialolithiasis-A Diagnostic Pitfall on Imaging: Report of Two Cases and Brief Review of the Literature - Thimsen, Vivian; Fauck, Vanessa; Wiesmüller, Marco; Agaimy, Abbas; Schapher, Mirco; Iro, Heinrich; Koch, Michael; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Objectives: Sialolithiasis is the most common cause of calcifications detected with ultrasound in patients with chronic inflammatory symptoms and swellings of the salivary glands. Other differential diagnoses of calcifications are extremely rare and mostly benign. Methods: Case report and literature review. Results: Two rare cases of malignant parotid gland tumors with calcifications in a localization typical for sialolithiasis, which were mistaken for salivary calculi based on image findings, are presented. Conclusions: This report intends to highlight the pitfalls in the imaging of parotid gland diseases. Even if malignant tumors of the parotid gland with calcifications are extremely rare, in ambiguous cases, differential diagnoses should be considered carefully. A high suspicion index of the need for further diagnostics in cases with calcifications is practical and could include missing periprandial symptoms, no obstruction signs in the proximal duct, and missing evidence of sialolithiasis in sialendoscopy.
CRIS-Team WoS Importer:2022-07-08

Does increasing the incidence of extracapsular dissection for benign tumors of the parotid correlate with an increased need for revision surgery? - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Goncalves, Miguel; Schapher, Mirco; Koch, Michael; Iro, Heinrich (Oral Oncology, 2019)
Objectives: The aim of this study was to investigate the hypothesis of whether extracapsular dissection (ED) of the parotid gland increases the need for revision surgery for benign tumours in comparison to traditional surgical modalities. A further aim of this study was to evaluate and compare the functional outcome of revision procedures after primary ED with other modalities involving the parotid gland in our department.
CRIS-Team WoS Importer:2019-06-21

Extracapsular Dissection in Pleomorphic Adenomas of the Parotid Gland: Results After 13 Years of Follow-up - Schapher, Mirco; Koch, Michael; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2020)
Objectives/Hypothesis: To assess long-term results after the treatment of parotid pleomorphic adenomas (PPAs) using different surgical techniques and focusing on recurrence rates and the risk of adverse effects. Study Design: Retrospective analysis. Methods: Retrospective analysis of 182 patients treated exclusively for PPAs at a tertiary referral center between 2000 and 2004. Thorough follow-up examinations over a mean period of 13 years were possible in 53.8% (n = 98/182). Tumors were categorized according to the European Salivary Gland Society (ESGS) system to improve the comparison of outcomes. After different surgical resection strategies, recurrence rates, postoperative facial nerve paresis (FNP), and incidence of Frey's syndrome were assessed. The follow-up period included clinical examinations and imaging of every patient in the treating department. Results: Of 182 patients, extracapsular dissection (ED) was performed in 29.7%, and other surgical modalities (OSMs), including facial nerve dissection, in 70.3%. After the long-term follow-up, 98% of all the patients (n = 96/98) were recurrence free. When recurrence rates were compared, no significant differences were noted (P <.331). ED resulted in significantly lower FNP rates compared to OSMs (P <.001). FNP rates significantly increased with size and location of the tumors according to ESGS categories (temporary and permanent FNP, P =.04). Surgical invasiveness corresponded to a significant increase in the incidence of Frey's syndrome (P <.001). Conclusions: ED was associated with the lowest complication rates, but not with a higher risk of recurrence, when compared with OSM in the long-term course. As ED can be performed in the majority of PPAs, it can be regarded as the treatment of choice whenever possible. Level of Evidence: 4 Laryngoscope, 2020.
CRIS-Team Scopus Importer:2020-05-22
Keywords: extracapsular dissection; facial nerve dissection; limited surgery; Parotid pleomorphic adenoma; recurrence

Going beyond extracapsular dissection in cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Traxdorf, Maximilian; Schapher, Mirco; Iro, Heinrich (Oral Oncology, 2019)
BACKGROUND: The aim of this study was to evaluate the potential for reducing surgical invasiveness in parotid cystadenolymphomas by means of capsular dissection based on the experience made in our department and on various aspects of these lesions gained from the relevant literature. METHODS: All patients treated for cystadenolymphomas with extracapsular or capsular dissection at a tertiary referral center between 2000 and 2017 were examined retrospectively. A literature review of various aspects and of different treatment strategies for this lesion was also performed. RESULTS: 629 patients were included in the study. 499 had solitary tumors (79.3%) and 130 had unilateral multicentric lesions (20.7%). 595 patients were managed by means of ED, while 34 patients underwent a CD. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 2.06% (13/629), all after extracapsular dissection, with a mean follow-up of 104.1 months. No statistical difference could be found between ED and CD in the overall occurrence rate of ipsilateral metachronous tumors or in the complication rate. No cases of a malignancy arising from a preexisting Warthin tumor could be detected in our study sample. CONCLUSION: A clear potential for reducing surgical invasiveness could be shown. A reliable imaging diagnosis, appropriate patient counseling and high compliance with close follow-up are the basic prerequisites for an acceptable outcome.
EVALuna2:35382

Histopathological comparison of pleomorphic adenomas of the parotid and submandibular gland - Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Ann Kristin; Müller, Susanna; Koch, Michael; Schapher, Mirco; Agaimy, Abbas; Iro, Heinrich (Oral Diseases, 2021)
Objective: The aim of this study was to investigate and compare the histopathological findings in pleomorphic adenomas (PA) of the parotid and submandibular gland with emphasis on the histological subtype and capsular characteristics. Materials and Methods: The histopathological specimens of all patients with PAs of the parotid and submandibular gland between 2000 and 2020 were re-examined by an experienced head and neck pathologist. Patients without representative slides allowing evaluation of the whole periphery of the PA were excluded from our study sample. Results: Nine hundred and thirty-four patients formed our study sample (327 men, 607 women, male-to-female ratio: 0.53:1). Eight hundred and forty-four cases had a PA in the parotid gland and the remaining 90 in the submandibular gland. Our comparative analysis showed that submandibular PAs are characterized by the consistent presence of an intact anatomical capsule, infrequent occurrence of pseudopodia and satellite nodules, and a low proportion of the high-risk myxoid subtype. Conclusion: Our study highlights significant differences between PAs of the parotid and submandibular glands in their histopathological characteristics. Their differences likely underlie the favorable surgical outcome observed in PAs of the submandibular glands and may explain the propensity of PAs of the parotid glands for local recurrences.
CRIS-Team Scopus Importer:2021-04-16
Keywords: capsule; parotid gland; pleomorphic adenoma; satellite nodules; submandibular gland

Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Zenk, Johannes; Bozzato, Alessandro; Kuenzel, Julian; Zengel, Pamela; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
Purpose The aim of this study was to assess the interrater reliability of ultrasound for diagnosing sialolithiasis. Materials and Methods A total of 100 consecutive patients with signs of obstructive sialadenopathy were evaluated. The patients all underwent ultrasound examinations in a standardized manner conducted by one specialist with extensive experience in the management of salivary gland disorders and proficiency in head and neck ultrasonography. The video recordings were sent to six colleagues with comparable experience without providing any further information about the patients' medical history and physical examination. Results The overall agreement between the seven observers was substantial, with a κ of 0.765 for the 100 cases and a percentage agreement level of 88.29 ± 3.01 % (range: 83-94 %). The range of agreement on this video set for observer pairs varied from substantial to almost perfect agreement (0.663 to 0.878). Among the few false-negative findings (5.4 %), 71.8 % were due to distal sialolithiasis. Two-thirds of the false-positive findings (3.7 %) were due to fibrotic stenosis. Conclusion The study confirmed the diagnostic value of ultrasound in sialolithiasis and demonstrated a very high level of interrater agreement, even in the absence of additional clinical patient information, thus further underscoring the importance of ultrasound as the examination of first choice in sialolithiasis.
CRIS-Team Scopus Importer:2019-08-16
Keywords: interrater; parotid; sialolithiasis; submandibular; ultrasound

Intraductal Fragmentation in Sialolithiasis Using Pneumatic Lithotripsy: Initial Experience and Results - Koch, Michael; Schapher, Mirco; Sievert, Matti; Mantsopoulos, Konstantinos; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2021)
Objective: To report initial experience in using a pneumatic lithotripter to treat salivary stones. Study Design: Level IV retrospective study. Setting: University hospital and tertiary referral center. Methods: A pneumatic lithotripter was used to treat salivary stones after these were diagnosed. Probes with diameters of 0.7 mm were used. Total fragmentation was intended in all stones. Stone fragments were removed using several instruments in serial sialendoscopies to achieve complete stone clearance. Results: A total of 62 patients with 77 stones were treated. Forty-three submandibular stones were treated in 34 patients, and 34 parotid stones were treated in 28 patients. An operating pressure of 2.5 bar and a single frequency mode were used. Complete fragmentation was achieved in all but one of the treated stones in both glands (98.7%). Among the patients, 90.32% became stone free and 100% symptom free. Multiple stones were treated in 24.19% of the patients, and multimodal therapy was also carried out in 24.19%. All of the glands were preserved. Conclusions: The pneumatic lithotripter proved to be effective in the treatment of sialolithiasis. Stone size, location, and the gland involved were important clinical factors. The device was sufficient to achieve success without any increased risk for complications in the patients or damage to the sialendoscopes.
CRIS-Team Scopus Importer:2021-10-22
Keywords: intraductal lithotripsy; pneumatic lithotripsy; salivary gland; sialendoscopy; sialolithiasis; treatment

Intraductal Lithotripsy in Sialolithiasis Using the Calculase III™ Ho:YAG Laser: First Experiences - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Iro, Heinrich (Lasers in Surgery and Medicine, 2020)
Background and Objectives: To report the first experiences with a newly available Ho:YAG laser system for the treatment of salivary stones. Study Design/Materials and Methods: A retrospective study in a tertiary referral center was conducted. Patients diagnosed with sialolithiasis were treated in Erlangen using the Calculase III™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany). Preset parameters had a frequency of 4 Hz and energy of 0.8–1.2 J, resulting in 3.2–4.8 W. Following total fragmentation, one to two serial sialendoscopies were performed to achieve complete fragment clearance. Results: A total of 55 stones in 49 patients were treated; 17 stones in 15 submandibular glands and 38 in 34 parotids. In total, 61 laser lithotripsies (range 1–3 per stone) were performed using various modes (long, short, and burst) and with preset parameters of 4 Hz and energy of 0.8–1.2 J, resulting in effective power of 3.2–4.8 W. Complete fragmentation was achieved in all the accessible stones. Sialendoscopes, fibers, or the mode used had no significant influence on success rates. A multimodal therapy concept was employed to treat stones in 12.24% of the cases; 95.92% of the patients were ultimately stone-free, and all became symptom-free. All glands were preserved. Conclusions: The new Calculase III™ Ho:YAG laser was effective in the treatment of sialolithiasis with no increased risk of complications in the patients or damage to the sialendoscopes. Clinical factors such as the type of gland involved, or the location and size of stones had a greater impact on success rates than the technical or preset parameters. Lasers Surg. Med. © 2020 Wiley Periodicals LLC.
CRIS-Team Scopus Importer:2020-10-09
Keywords: intraductal lithotripsy; laser; salivary gland; sialendoscopy; sialolithiasis; treatment

Intraductal Pneumatic Lithotripsy after Extended Transoral Duct Surgery in Submandibular Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2018)
Objective Persistent, residual, or recurrent stones after transoral duct surgery are always associated with hilar to intraparenchymal and/or multiple sialolithiasis, causing difficulties in the treatment. This study was performed to assess the value of intraductal lithotripsy in the treatment of persistent, residual, or recurrent sialolithiasis after extended duct surgery in the submandibular gland. Study Design Retrospective study covering February 2015 to June 2018. Study Setting Tertiary referral center for salivary gland diseases. Subjects and Methods After extended ductal surgery, 39 patients presenting with persistent, residual, or recurrent stones were treated. Four patients had persistent stones; 16 had residual stones; and 19 presented with recurrent stones. Among these patients, 50 stones were treated with intraductal pneumatic lithotripsy. Fragmentation rate, stone-free rate, and symptom-free rate after treatment with intraductal lithotripsy were outcome measures. Results Of the 39 patients, 97.4% became stone-free, and all were symptom-free. Ninety-eight percent of the stones were completely fragmented. For 23.1% of the patients, >1 stone was treated with intraductal lithotripsy. All patients with persistent stones, 93.7% of those with residual stones, and all with recurrent stones became stone-free and symptom-free. No severe complications developed. Conclusions This study shows that patients presenting with difficult and/or multiple sialolithiasis after extended transoral submandibular duct surgery can be treated with success rates >97%. For multiple sialolithiasis in particular, a multimodal treatment approach with interventional sialendoscopy and intraductal lithotripsy as a central element is a prerequisite for success, as this enables the most difficult part to be performed with high success rates.
EVALuna2:35383

Intraductal pneumatic lithotripsy for salivary stones with the StoneBreaker: Preliminary experience - Koch, Michael; Mantsopoulos, Konstantinos; Schapher, Mirco; Von Scotti, Felix; Iro, Heinrich (Laryngoscope, 2016)
OBJECTIVES/HYPOTHESIS: To test the effectiveness of a newly approved pneumatic lithotripter for fragmentation of salivary stones. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: In 44 patients, 49 stones were primarily treated with direct endoscopic guidance using the StoneBreaker. Twenty-three stones were located in the parotid gland and 26 in the submandibular gland. RESULTS: Complete fragmentation was achieved combined extracorporeal in 97.7% of the stones. All of the patients became symptom free, and 97.7% were stone free. Three patients underwent lithotripsy procedures. Altogether additional treatment was necessary in five cases to achieve stone clearance. The reason for residual sialolithiasis was intraparenchymal repulsion of a residual fragment (n = 1). The glands were preserved in all cases. CONCLUSIONS: Endoscopically guided intraductal pneumatic lithotripsy using the StoneBreaker is an effective and promising procedure for the treatment of sialolithiasis. LEVEL OF EVIDENCE: 4 Laryngoscope, 126:1545-1550, 2016.
EVALuna2:33186

Investigation of Sonographic Criteria for Reliable Identification of T1–T2 Low-Grade Malignant Tumors of the Parotid Gland - Berner, Ferdinand; Koch, Michael; Müller, Sarina Katrin; Schapher, Mirco; Grundtner, Philipp; Iro, Heinrich; Mantsopoulos, Konstantinos (Ultrasound in Medicine and Biology, 2020)
The aim of this study was to investigate sonographic findings of low-grade malignant tumors of the parotid gland. The sonographic findings of all patients treated for T1–T2 low-grade carcinomas of the parotid gland between 2003 and 2018 were retrospectively examined and compared with those of patients with pleomorphic adenomas for the following parameters: definition of tumor margins, echotexture, echogenicity, shape and vascularization. Statistical analysis was performed using the χ2 test. A p value of <0.05 was considered statistically significant. A total of 310 patients (62 with T1–T2 low-grade malignant tumors, 248 with pleomorphic adenomas) were evaluated. Our analysis detected a statistically significant difference in the definition of margins, echotexture, echogenicity and shape. Furthermore, we could detect a specific pattern (anechoic islets in a small hypoechoic lesion with distal enhancement) appearing far more frequently in low-grade malignant lesions. It seems that there is still potential to reduce the incidence of the false working hypothesis “benign lesion” on imaging of low-grade malignant tumors.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Acinic cell carcinoma; Mucoepidermoid carcinoma; Parotid gland; Pleomorphic adenoma; Ultrasound

Is extracapsular dissection for pleomorphic adenoma rather a euphemism for enucleation that jeopardises the intactness of the capsule? - Mantsopoulos, Konstantinos; Iro, A. K.; Sievert, Matti; Müller, Sarina Katrin; Agaimy, Abbas; Schapher, Mirco; Koch, Matthias; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2021)
The aim of this study was to compare several surgical modalities with respect to the incidence of positive margins and focal capsular exposure of pleomorphic adenoma of the parotid gland. The clinical records and histopathological findings of all patients who underwent parotidectomy for pleomorphic adenoma between 2006 and 2020 were retrospectively evaluated (n = 845). The lesion was removed by extracapsular dissection in 577 cases (68%) and facial nerve dissection in 268 (32%). Our analysis did not reveal a statistically significant difference between the examined modalities regarding positive margins (p=0.648) or capsular exposure (p=0.112). Recurrences were detected in 7/845 cases (0.82%) with a mean (range) follow-up time of 82.3 (6-183) months. The choice of surgical method does not seem to have a significant effect on the incidence of positive margins, or on the capsular exposure of a pleomorphic adenoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: capsule; complete parotidectomy; extracapsular dissection; partial superficial parotidectomy; pleomorphic adenoma; superficial parotidectomy

Long-term oncologic and functional outcome in pleomorphic adenomas of the submandibular gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich (Laryngoscope, 2017)
Objectives: The aim of the study was to evaluate the oncologic and functional long-term outcome after surgical therapy of pleomorphic adenomas of the submandibular gland. Methods: The medical charts of all patients treated for pleomorphic adenomas of the submandibular gland by means of submandibulectomy between 2000 and 2016 were studied retrospectively. Patients who had had revision after external primary surgery, as well as patients with insufficient data were excluded from our study sample. Results: A total of 75 patients formed our study sample (28 men, 47 women, male:female ratio 0.59:1). Their mean age was 48 years (14-78 years). Mean follow-up was 82 months (12-170 months). No recurrences of a pleomorphic adenoma could be detected in our study cases. Normal facial nerve function (House-Brackmann grade I) in the direct postoperative phase was shown in 54/75 cases (72%). In the remaining 21/75 cases (28%), mild paresis of the marginal mandibular branch of the facial nerve (House-Brackmann II) could be detected in the direct postoperative phase. All cases with facial palsy had recovered with normal facial nerve function (House-Brackmann I) in 3-6 months. Conclusion: Our study was able to show oncologic and consistently acceptable oncologic and functional outcomes after submandibulectomy for pleomorphic adenomas of the submandibular gland. Level of Evidence: 4.
EVALuna2:33360

Minimally Invasive Interventions in Obstructive and Inflammatory Salivary Gland Diseases: Local Anesthesia Based Pain Management, Stratification of Invasiveness, and Patients’ Perceptions - Schapher, Mirco; Traxdorf, Maximilian; Iro, Heinrich; Koch, Michael (Journal of Clinical Medicine, 2025)
Objectives: Since the peri- and intraoperative management of patients with inflammatory and obstructive sialadenitis (IOS) differs significantly between treating centers worldwide, we investigated whether these patients can be treated successfully, resource-savingly and with high patient satisfaction using minimally invasive procedures under local anesthesia (LA). Methods: We developed a comprehensive, stratified routine anesthesia and pain management protocol based on our proposed classification of invasiveness (grade 1–4), for almost all available IOS treatment procedures. We included 377 patients with 470 LA-conducted interventions in our study and evaluated their perceptions during and after the treatment. Results: The protocol was applied to all 377 study participants for all 470 interventions. The mean grade of invasiveness was 2.49 ± 1.31, with a mean procedure duration of 30 ± 20 min. We found a significant positive association between invasiveness levels and procedure duration (p = 0.001) or pain directly after surgery (p = 0.004). Patients rated the procedures as ”well acceptable” or better in a large majority (88.1–97%) regarding the administration and potency of LA, procedure duration, and pain during and directly after surgery. In total, 96.4% of patients would have the treatment repeated under the same conditions. Conclusions: The proposed anesthesia and pain management regimen, respecting invasiveness levels, enables IOS patients to undergo treatment under LA with high success rates, serving as a potential guide for performing physicians.
CRIS-Team Scopus Importer:2025-04-11
Keywords: inflammatory and obstructive salivary gland diseases; local anesthesia; minimal invasive treatment; pain management; patients’ perceptions; sialadenitis; sialendoscopy; sialodochitis; sialolithiasis

Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17

Multimodal treatment in difficult sialolithiasis: Role of extracorporeal shock-wave lithotripsy and intraductal pneumatic lithotripsy - Schapher, Mirco; Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; von Scotti, Felix; Goncalves, Miguel; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES: To assess results after treatment of difficult/complex sialolithiasis with extracorporeal shock-wave lithotripsy (ESWL) and intraductal pneumatic lithotripsy (IPL). STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: Altogether, 63 stones were diagnosed in 38 patients with difficult/complex sialolithiasis. Forty-nine stones were treated with fragmentation using both ESWL and IPL. Stones accessible with the sialendoscope were treated primarily with IPL in multiple sialolithiasis. RESULTS: Seventy-one ESWL procedures and 57 IPL were performed in our patients. Forty-nine stones were treated by 67 ESWL procedures and 52 IPL. ESWL converted sialoliths from sialendoscopically untreatable into sialendoscopically treatable cases in 94.7%; the treatment then was completed by a total of 52 IPL procedures. ESWL was performed before IPL (81.6%), in combination with IPL (7.9%) and after (10.5%). Complete fragmentation was achieved in 97.9%. Four stones each were treated with ESWL and IPL alone in multiple sialolithiasis. Altogether, 53 stones were treated by 57 IPL procedures. Complete fragmentation was achieved in 98.1% of the 53 stones. ESWL and IPL were the dominant treatment modalities in 84.1% of all 63 stones treated. Of all 38 patients, 92.1% became stone-free and all became symptom-free. All the glands were preserved. Multiple stones were treated in 34.2% of the patients; of these, 92.3% became stone-free. CONCLUSION: These results show that patients with difficult and complex sialolithiasis can be treated with high success rates of > 90% using a multimodal, minimally invasive, and gland-preserving treatment approach. ESWL and IPL played a key role in this multimodal treatment regime in > 80% of stones. LEVEL OF EVIDENCE: 4. Laryngoscope, 2017.
EVALuna2:33362

Nearly 3,000 salivary stones: some clinical and epidemiologic aspects - Sigismund, Paolo E.; Zenk, Johannes; Koch, Michael; Schapher, Mirco; Rudes, Mihael; Iro, Heinrich (Laryngoscope, 2015)
To investigate epidemiological features and symptoms of sialolithiasis and their implications for diagnosis and management.Retrospective cohort study.Retrospective analysis on 2,322 patients with sialolithiasis, between 1987 and 2009. The statistical significance between two sample distributions was computed using analysis of variance Student t test for two-tailed distribution.A total of 2,959 calculi were identified by means of ultrasound. Of those, 80.4% were located in the submandibular duct system (53% hilar/proximal, 37% distal, 10% intraparenchymal) and 19.6% were parotid stones (83% in Stensen's duct, 17% intraparenchymal). Sialoliths had been discovered beforehand in the submandibular gland (P = 0.00024; t test). Symptoms, measured from first visit, lasted on average 26 months (range: 1 day-30 years). The main group suffered from swelling (50.3%), followed by painful swelling (41.6%) and pain (3.1%). Multiple stones were found in 16.9% of patients (18.1% in the submandibular gland; 14.3% in the parotid). Average stone diameter in the submandibular gland was 8.3 mm (range 1-35 mm), and the stones were in Lustmann group II (46%). In the parotid gland, the average diameter was 6.4 mm (range 1-31 mm), and 51% were in Lustmann group I.Nowadays, epidemiologic features and clinical manifestations of sialolithiasis play an important role, assisting not only in diagnosis but also in determining appropriate treatment. Due to their location and smaller diameter, parotid stones in some cases can only be treated using a mini-invasive endoscopic technique. Submandibular stones more often require a combined approach.4
EVALuna2:19993

Neutrophil Extracellular Traps Drive Dacryolithiasis - Zlatar, Leticija; Timm, Thomas; Lochnit, Günter; Bilyy, Rostyslav; Bäuerle, Tobias; Munoz Becerra, Marco; Schett, Georg; Knopf, Jasmin; Heichel, Jens; Ali, Mohammad Javed; Schapher, Mirco; Paulsen, Friedrich; et al. (Cells, 2023)
Mucopeptide concretions, previously called dacryoliths, are macroscopic stones that commonly obstruct the lacrimal sac. The mechanism behind dacryolithiasis remains unclear; however, the involvement of various immune cells, including neutrophils, has been confirmed. These findings remain limited, and no information on neutrophil extracellular traps (NETs), essentially involved in the pathogenesis of other lithiases, is available yet. Here, we employ microcomputed tomography, magnetic resonance tomography, histochemistry, mass spectrometry, and enzyme activity analyses to investigate the role of neutrophils and NETs in dacryolithiasis. We classify mucopeptide concretions into three types, with respect to the quantity of cellular and acellular material, polysaccharides, and mucosubstances. We propose the role of neutrophils and NETs within the existing model of gradual formation and growth of mucopeptide concretions, with neutrophils contributing to the initial stages of dacryolithiasis, as they localized on the inner (older) parts of the tissue. As NETs localized on the outer (newer) parts of the tissue, we link their role to the late stages of dacryolithiasis, presumably maintaining the proinflammatory environment and preventing efficient clearance. An abundance of IgG on the surface indicates the involvement of the adaptive immune system later as well. These findings bring new perspectives on dacryolithiasis, in which the innate and adaptive immune system are essentially involved.
CRIS-Team Scopus Importer:2023-08-11
Keywords: dacryolithiasis; dacryoliths; lacrimal sac; mucopeptide concretions; neutrophil extracellular traps; neutrophils

Neutrophil Extracellular Traps Promote the Development and Growth of Human Salivary Stones - Schapher, Mirco; Koch, Michael; Weidner, Daniela; Scholz, Michael; Wirtz, Stefan; Mahajan, Aparna; Herrmann, Irmgard; Singh, Jeeshan; Knopf, Jasmin; Leppkes, Moritz; Grüneboom, Anika; Alexiou, Christoph; et al. (Cells, 2020)
Salivary gland stones, or sialoliths, are the most common cause of the obstruction of salivary glands. The mechanism behind the formation of sialoliths has been elusive. Symptomatic sialolithiasis has a prevalence of 0.45% in the general population, is characterized by recurrent painful periprandial swelling of the affected gland, and often results in sialadenitis with the need for surgical intervention. Here, we show by the use of immunohistochemistry, immunofluorescence, computed tomography (CT) scans and reconstructions, special dye techniques, bacterial genotyping, and enzyme activity analyses that neutrophil extracellular traps (NETs) initiate the formation and growth of sialoliths in humans. The deposition of neutrophil granulocyte extracellular DNA around small crystals results in the dense aggregation of the latter, and the subsequent mineralization creates alternating layers of dense mineral, which are predominantly calcium salt deposits and DNA. The further agglomeration and appositional growth of these structures promotes the development of macroscopic sialoliths that finally occlude the efferent ducts of the salivary glands, causing clinical symptoms and salivary gland dysfunction. These findings provide an entirely novel insight into the mechanism of sialolithogenesis, in which an immune system-mediated response essentially participates in the physicochemical process of concrement formation and growth.
CRIS-Team Scopus Importer:2020-10-09
Keywords: lithogenesis; neutrophil extracellular traps; neutrophils; salivary glands; salivary stones; sialadenitis; sialolithiasis; stone development; stone growth

Papillary stenosis of the submandibular gland caused by dental prostheses - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objectives: The aim of this study was to assess diagnosis and treatment of submandibular duct stenosis caused by dental prostheses. Study Design: This retrospective study included 9 patients with papillary stenosis caused by physical irritation of the Wharton duct ostium by a mandibular dental prosthesis. Diagnostics included physical examination, as well as transcutaneous and transoral ultrasound examinations. Treatment consisted of duct incision, papillotomy, and subsequent sialendoscopy. After surgery, patients were advised to have the dental prosthesis altered by the dentist and to have regular gland massage. Follow-up data were obtained via telephone interviews. The most important outcome parameter was a symptom-free state. Results: In all 9 patients, the insertion of the sialendoscope was initially impossible because of the stenosis. After duct incision, sialendoscopy ruled out other obstructive causes and inflammatory states, leaving the dental prosthesis as the only underlying cause of the obstruction. Seven of the 9 treated patients were interviewed after a follow-up period of 28.1 (± 25.4) months. The procedures had resulted in all patients being symptom-free, without any reported complications. Conclusions: Mandibular prostheses can cause stenosis of the papillary region with subsequent submandibular duct obstruction. Surgical therapy is easy to perform and results in excellent long-term outcomes.
CRIS-Team Scopus Importer:2020-03-06

Parotid pleomorphic adenomas: Factors influencing surgical techniques, morbidity, and long-term outcome relative to the new ESGS classification in a retrospective study - Schapher, Mirco; Koch, Michael; Agaimy, Abbas; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Journal of Cranio-Maxillofacial Surgery, 2019)
Purpose: To assess long-term results after treatment of parotid pleomorphic adenomas (PPAs) with different surgical techniques, standardized according to the European Salivary Gland Society (ESGS) classification system. Methods: We analyzed ESGS categories, occurrence of facial nerve paresis (FNP), Frey's syndrome, histopathology, and recurrences. Surgical modalities were compared, differentiating techniques with and without facial nerve dissection. A strict protocol ensured a postoperative follow-up-period of more than 7 years. Results: 205 patients were included. A complete follow-up was possible in 138 patients, 77 of whom underwent extracapsular dissection (ED) and 61 of whom had other surgical modalities (OSMs). ESGS categories correlated with the extent of surgery, significantly with the risk for FNP and Frey's syndrome, but not with recurrences. Recurrences did not differ significantly between ED and OSMs, whereas the risks for FNP (p < 0.001 each) and Frey's syndrome (p = 0.000) were significantly higher after OSMs in comparison with ED. Young women with a stroma-rich (myxoid) tumor subtype appear to have the greatest risk for recurrences. Conclusion: ED is the treatment of choice for PPAs, if possible, resulting in similar recurrence rates but significantly fewer comorbidities in comparison with more extensive surgery. After the treatment of PPAs, a long-term follow-up is needed, including imaging.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Extracapsular dissection; Facial nerve paresis; Follow-up; Frey's syndrome; Pleomorphic adenoma; Recurrence

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

Pneumoparotid: Practical impact of Surgeon performed Ultrasound in an effective Diagnostic Approach - Goncalves, Miguel; Sievert, Matti; Mantsopoulos, Konstantinos; Schapher, Mirco; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael (Oral Diseases, 2022)
Objectives: Pneumoparotid is characterized by air inclusions in the parotid duct system. Use of ultrasound has proved valuable for evaluating air inclusions in various parts of the body; the diagnostics of this condition has not been systematically analyzed, however. The aim of this study was to evaluate the value of ultrasound in the detection of air inclusions along the parotid duct system and its closer characterization. Methods: Retrospective analysis was carried out of patients diagnosed with pneumoparotid between 2005 and 2020 in a salivary gland center. Ultrasound was performed in all cases, and features of air inclusions were described. Reference standard was the clinical demonstration of foamy saliva after gland massage and/or sialendoscopic evidence of intraductal air inclusions. Results: Twenty-one patients were identified (48.8 ± 3.8 years). Two were associated with wind instruments; seven were iatrogenic, following treatment for duct stenosis; one after radiotherapy; four with known bruxism and seven were idiopathic and without associated conditions. On ultrasound examination, pneumoparotid was characterized by three phenomena: flattened, mobile hyperechoic reflexes, dirty shadows with reverberation or “sunbeam effect,” and shifting shadows during gland massage. Conclusions: Ultrasound was useful for characterizing pneumoparotid in a fast and practical way and could serve as imaging tool of first choice.
CRIS-Team Scopus Importer:2022-07-15
Keywords: diagnostics; parotid gland; pneumoparotid; ultrasound

Primary parotid gland lymphoma: pitfalls in the use of ultrasound imaging by a great pretender - Mantsopoulos, Konstantinos; Koch, M.; Fauck, Vanessa; Schinz, Katharina; Schapher, Mirco; Constantinidis, J.; Rösler, Wolf; Iro, Heinrich (International journal of oral and maxillofacial surgery, 2020)
The aim of this study was to highlight several misleading imaging and clinical aspects of parotid gland lymphoma, taking our personal experience and relevant literature reports into consideration. The records of all patients diagnosed with lymphoma in the parotid gland between 2005 and 2017 were examined retrospectively. Sixty-seven patients were included in this study. The mean age was 61.4 years. The most frequent histological entities were marginal zone B-cell lymphoma (31.3%) and follicular lymphoma (28.4%). The tumour was stage I in 35 cases (52.2%), stage II in 13 cases (19.4%), stage III in 11 cases (16.4%), and stage IV in eight cases (11.9%). B symptoms were seen in only three patients (4.5%). The diagnosis was made after parotidectomy in 51 cases (76.1%), by core needle biopsy in 14 cases (20.9%), and by means of open biopsy in the remaining two cases (3.0%). Parotid gland lymphoma represents a diagnostically challenging, multifaceted entity that can easily mimic both benign and malignant conditions. This entity should be included in the differential diagnosis of almost all types of parotid lesion, as it seems to play the role of a great pretender.
CRIS-Team Scopus Importer:2021-04-19
Keywords: diffuse large B-cell lymphoma; follicular lymphoma; lymphoma; MALT lymphoma; marginal zone B-cell lymphoma; parotid gland; parotidectomy; ultrasound

Qualität in der Befundung von Kopf- und Halssonographien an Universitätskliniken – eine Stichprobe - Künzel, J.; Bozzato, A.; Ernst, B. P.; Fuhrmann, T.; Ugele, I.; Scherl, C.; Schapher, Mirco; Volk, G. F.; Mansour, N.; Knopf, A.; Bohr, C.; Hamann, K. F. (HNO, 2021)
Background: Ultrasound diagnostics are widely used and are standard for radiologists, otolaryngologists, and oral and maxillofacial surgeons in the diagnostic work-up of various pathologies. There is agreement that digital documentation is urgently needed at present to improve and standardize the quality of sonographic documentation. There are more and more publications on the implementation of standardized documentation of findings in imaging diagnostics, including head and neck sonography. Objective: The present work aims to determine the quality of routine head and neck sonography findings on a random basis, according to the criteria of the Bavarian Association of Statutory Health Insurance Physicians (KVB) at a selection of German university otolaryngology departments (ENT). Materials and methods: A total of 70 randomly selected anonymized written findings including image documentation from seven ENT departments were retrospectively analyzed by an experienced KVB examiner concerning fulfilment of KVB criteria. The data were evaluated descriptively. Results: Of the 70 reports, 69 were eligible for evaluation. The average documentation completeness was 80.6%. A total of 9 findings were correctly documented in full (13%). The documentation completeness of the individual departments was sorted in ascending order from 68.1% to 93%. With 88.5% vs. 75%, the hospitals with a structured report showed a higher level of completeness. In 75% of the cases the hospitals with structured reports also had digital solutions for reporting and image archiving. Conclusion: In general, there is potential for optimization regarding the completeness and quality of routinely prepared head and neck sonography findings at the selected university ENT departments. The implementation of structured reporting masks and the conversion of analogue documentation into digital solutions as well as digital networking with the hospital information systems, picture archiving and communication systems should be promoted. Supervision by senior doctors is required to ensure the quality of findings of inexperienced colleagues and to help to achieve standards in reporting.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Completeness of findings; Digital documentation of findings; Quality of findings; Structured reporting; Ultrasound training

Response to Letter to the editor: Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis: Methodological Issues. Interrater Reliability of Ultrasound: Methodological Issues - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
CRIS-Team Scopus Importer:2019-10-18

Simultaneous Application of Ultrasound and Sialendoscopy and its Value in the Management of Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Ultraschall in der Medizin, 2020)
Objective Ultrasound (US) and sialendoscopy (SE) are routinely used in patients presenting with sialolithiasis in the submandibular (SMG) and parotid gland (PG). The objective was to assess the value of the simultaneous application of US and SE in the management of sialolithiasis. Study Design Retrospective study. Setting: Tertiary referral center for salivary gland diseases. Participants: Patients in whom US and SE as single investigation tools were neither conclusive nor useful in the management of sialolithiasis were investigated using both methods simultaneously (simUS + SE). Main outcome measures: Establishment of the final diagnosis and/or contribution to the planning/performing of treatment in sialolithiasis. Results 74 patients were examined by simUS + SE (58.1 % SMG and 41.9 % PG). In all patients (unclear) hyperechoic reflexes were assessed and/or localized by SE-controlled US na-vigation. 68.9 % of the patients were investigated for diagnostic or differential-diagnostic reasons including distinguishing extraductal from intraductal calcifications and/or to exclude residual stones after therapy. In 52.7 % simUS + SE was used to plan and/or perform further treatment, in 20.3 % to enable performing a combined approach (all PG) and in 29.7 % to evaluate and plan the most adequate therapy (mainly intraductal vs. extracorporeal shock wave lithotripsy, 68.2 % of these SMG). In two cases SE-controlled and US-guided stone extraction was performed. Conclusion SimUS + SE is an innovative approach which proved to be very useful in managing sialolithiasis. It added valuable information regarding the establishment of a diagnosis or differential diagnosis, planning and performing the most adequate treatment, intraoperative control of therapy and postoperative follow-up.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Diagnosis; Salivary gland; Sialendoscopy; Therapy; Ultrasound

Simultaneous application of ultrasound and sialendoscopy: experience in the management of stenosis and other non-sialolithiasis-related salivary gland disorders - Koch, M.; Schapher, Mirco; Goncalves, Miguel; Iro, Heinrich; Mantsopoulos, K. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: To assess the value of the simultaneous application of ultrasound and sialendoscopy (US+SE) in several salivary gland diseases not caused either by sialolithiasis or by tumours. PATIENTS AND METHODS: US+SE are routinely used in patients with inflammatory, obstructive, and other non-tumorous major salivary gland diseases. In patients in whom US and SE as single investigation tools were not conclusive or not useful in the management of several non-sialolithiasis-related conditions (stenoses, ductal anomalies, ductal trauma, space-occupying paraductal lesions), both methods were used simultaneously for diagnosis and treatment. RESULTS: US+SE were used simultaneously in 44 patients for 56 indications. Stenosis was managed in 36 cases (81.8%) and in thirty-eight of the indications (67.9%) with simultaneous US+SE. The successful opening was achieved in 23 (63.9%), conservative and/or ablative treatment was indicated in 13 (36.1%), and further imaging was indicated in two (5.5%) of these cases. Post-traumatic or postinfectious complications were managed in 12 (27.3%) of all cases, and isolated ductal anomalies and paraductal space-occupying lesions were assessed in three cases (8.3%) each. In all instances, simultaneous US+SE clearly improved the management in diagnosis and/or therapy. CONCLUSIONS: Simultaneous application of US+SE provided additional information that proved to be valuable for diagnosis, planning, and treatment in several non-sialolithiasis-related conditions such as stenoses, ductal anomalies, ductal trauma, and space-occupying paraductal lesions.
CRIS-Team Scopus Importer:2020-03-31

The current value of quantitative shear wave sonoelastography in parotid gland tumors - Thimsen, Vivian; Goncalves, Miguel; Koch, Michael; Mantsopoulos, Konstantinos; Hornung, Joachim; Iro, Heinrich; Schapher, Mirco (Gland Surgery, 2021)
Background: The preoperative differentiation between salivary gland tumor entities using computed tomography, magnetic resonance imaging (MRI) and ultrasound ( US) is still limited. Biopsies are often regarded as indispensable for properly characterizing these various lesions. The aim of this study was to analyze the value of acoustic radiation force impulse (ARFI) sonoelastography as an US differentiation tool when examining parotid gland (PG) lesions.
CRIS-Team WoS Importer:2021-05-28

The Translational Role of MUC8 in Salivary Glands: A Potential Biomarker for Salivary Stone Disease? - Schicht, Martin; Reichle, Adrian; Schapher, Mirco; Garreis, Fabian; Kleinsasser, Benedikt; Aydin, Malik; Sahin, Afsun; Iro, Heinrich; Paulsen, Friedrich (Diagnostics, 2021)
Mucin (MUC) 8 has been shown to play an important role in respiratory disease and inflammatory responses. In the present study, we investigated the question of whether MUC8 is also produced and secreted by salivary glands and whether it may also play a role in the oral cavity in the context of inflammatory processes or in the context of salivary stone formation. Tissue samples from parotid and submandibular glands of body donors (n = 6, age range 63-88 years), as well as surgically removed salivary stones from patients (n = 38, age range 48-72 years) with parotid and submandibular stone disease were immunohistochemically analyzed targeting MUC8 and TNF alpha. The presence of MUC8 in salivary stones was additionally analyzed by dot blot analyses. Moreover, saliva samples from patients (n = 10, age range 51-72 years), who had a salivary stone of the submandibular gland on one side were compared with saliva samples from the other "healthy " side, which did not have a salivary stone, by ELISA. Positive MUC8 was detectable in the inter- and intralobular excretory ducts of both glands (parotid and submandibular). The glandular acini showed no reactivity. TNF alpha revealed comparable reactivity to MUC8 in the glandular excretory ducts and also did not react in glandular acini. Salivary stones demonstrated a characteristic distribution pattern of MUC8 that differed between parotid and submandibular salivary stones. The mean MUC8 concentration was 71.06 ng/mL in female and 33.21 ng/mL in male subjects (p = 0.156). Saliva from the side with salivary calculi contained significantly (15-fold) higher MUC8 concentration levels than saliva from the healthy side (p = 0.0005). MUC8 concentration in salivary stones varied from 4.59 ng/mL to 202.83 ng/mL. In females, the MUC8 concentration in salivary stones was significantly (2.3-fold) higher, with an average of 82.84 ng/mL compared to 25.27 ng/mL in male patients (p = 0.034). MUC8 is secreted in the excretory duct system of salivary glands and released into saliva. Importantly, MUC8 salivary concentrations vary greatly between individuals. In addition, the MUC8 concentration is gender-dependent (& FEMALE; > & MALE;). In the context of salivary stone diseases, MUC8 is highly secreted in saliva. The findings support a role for MUC8 in the context of inflammatory events and salivary stone formation. The findings allow conclusions on a gender-dependent component of MUC8.
CRIS-Team WoS Importer:2022-01-14

Toxic retrobulbar neuritis due to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-based chronic sinusitis in the left sphenoid sinus: a case report - Schapher, Mirco; Brügel, Jacob; Güner, Fabian; Volbers, Bastian; Eichhorn, Philip; Agaimy, Abbas; Berger, Magdalena; Mardin, Christian; Dörfler, Arnd; Hock, Stefan (Journal of Medical Case Reports, 2023)
BACKGROUND: Abrupt visual impairment constitutes a medical urgency, necessitating an interdisciplinary diagnostic and therapeutic approach owing to the broad spectrum of potential etiologies, thereby engaging numerous medical specialties. CASE PRESENTATION: A 21-year-old Mixed White and Asian female patient, with medical history of nonsteroidal antiinflammatory drug-exacerbated respiratory disease necessitating previous sinus surgery, reported sudden monocular vision loss. Unremarkable ophthalmological examination of the fellow eye and hematological parameters, save for a slight elevation in lymphocytes and eosinophils, were observed. Imaging studies indicated recurrence of bilateral chronic rhinosinusitis with nasal polyps and a mucocele in the left sphenoid sinus, accompanied by bony structural deficits. Emergency revision sinus surgery, guided by navigation, was promptly performed. The patient received treatment with methylprednisolone, ceftriaxone, cyanocobalamin, pyridoxine, thiamine, and acetylsalicylic acid. During the hospital stay, she developed steroid-induced glaucoma, which was subsequently managed successfully. Negative microbiological swabs, along with pathohistological evidence of increased tissue eosinophilia and the patient's clinical history, led to the diagnosis of toxic retrobulbar neuritis secondary to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-associated chronic rhinosinusitis of the left sphenoid sinus. CONCLUSIONS: In cases of acute unilateral vision loss, optic neuritis is a highly probable differential diagnosis and may be induced by pathologies of the paranasal sinuses. Nonsteroidal antiinflammatory drug-exacerbated respiratory disease, a subtype of chronic rhinosinusitis, is associated with type 2 inflammation, which is increasingly recognized for its role in the pathogenesis of bronchial asthma, eosinophilic esophagitis, and atopic eczema. Clinicians should consider chronic rhinosinusitis as a potential differential diagnosis in unilateral visual loss and be cognizant of the rising significance of type 2 inflammations, which are relevant to a variety of diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blindness; Case report; Inflammation mediators; Neuritis; Optic; Sinusitis

Transoral submandibulotomy for deep hilar submandibular gland sialolithiasis - Schapher, Mirco; Mantsopoulos, Konstantinos; Meßbacher, Maria-Elena; Iro, Heinrich; Koch, Michael (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: To assess the long-term results after transoral submandibulotomy for stones located in the deep hilar and intraparenchymal submandibular region. STUDY DESIGN: Retrospective cohort analysis. METHODS: Retrospective evaluation including all patients treated with transoral submandibulotomy for sialolithiasis at a tertiary referral center. RESULTS: Complete stone removal at the first transoral surgical treatment was achieved in 185 of 234 patients (79.1%). One hundred seventy-five of the 234 patients were followed up for a mean of 31.2 ( ± 20.5) months. During the follow-up period, 140 of the 175 patients (80.0%) became symptom free after one operation. In patients with residual symptoms, no further treatment was needed in 12 patients (6.9%) due to the mildness of the symptoms; 23 patients (13.1%) received further therapy, which was successful in 15 cases. Submandibulectomy only had to be performed in 3.4% of the patients with follow-up (6/175). In a questionnaire survey, 91.4% of the patients stated that they would be prepared to have the same operation again. CONCLUSIONS: These findings show that transoral removal of submandibular sialoliths located in the deep hilum or adjacent intraglandular parenchyma is an effective treatment that can be assisted by additional measures. The techniques described show high success rates, good long-term results, low complication rates, and they avoided the need for submandibulectomy in >95% of cases. LEVEL OF EVIDENCE: 4. Laryngoscope, 127:2038-2044, 2017.
EVALuna2:33207

Transoral ultrasound: a helpful and easy diagnostic method in obstructive salivary gland diseases - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (European Radiology, 2019)
• Transoral ultrasound is a simple technique, very helpful for the evaluation of obstructive diseases of the salivary glands. • It overcomes most of the limitations of transcutaneous ultrasound.
CRIS-Team Scopus Importer:2019-05-02

Transoral Ultrasound in the Diagnosis of Obstructive Salivary Gland Pathologies - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Ultrasound in Medicine and Biology, 2019)
Transcutaneous ultrasound (TCUS) is an accepted diagnostic method in salivary gland diseases. However, sparse data are available on the use of transoral ultrasound (TOUS) in sialadenopathies. One hundred five patients presenting with various obstructive sialadenopathies were examined using TOUS and TCUS. Ultrasound findings were validated by direct visualization in subsequent sialendoscopy examinations. By TOUS, but not by TCUS, all patients with sialolithiasis (70/105) could be identified and virtually all concrements, even very small ones, were detected and distinguished from artifacts. Ductal stenoses (16/105) could be correctly differentiated from sialoliths, and exceptional insights into the delicate anatomy of parotid duct stenoses were gained. TOUS provided detailed information on other space-occupying lesions (14/105) and circumvented the method-related diagnostic weaknesses of TCUS. As a valuable tool in the diagnosis of obstructive sialadenopathies, TOUS seems superior to TCUS in pathologies involving the distal parotid duct, the submandibular duct system and the floor of the mouth.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Obstructive sialadenopathy; Salivary duct stenosis; Salivary glands; Sialolithiasis; Transoral ultrasound

Ultrasound in inflammatory and obstructive salivary gland diseases: Own experiences and a review of the literature - Koch, Michael; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos; Schapher, Mirco (Journal of Clinical Medicine, 2021)
Background: Ultrasound is established as a diagnostic tool in salivary glands for obstructive diseases such as sialolithiasis and tumors. Concerning inflammatory diseases and in non-sialolithiasis-caused obstruction, much fewer data are available. In recent years, technical devel-opment has allowed a better assessment of the gland parenchyma, and knowledge about intraductal pathologies has increased considerably, which has provided new insights and a new interpretation of ultrasound findings. Objectives: To provide a comprehensive review of the literature that in-cludes our own experiences and to point out the state of the art in ultrasound in the diagnostics of inflammatory and obstructive salivary gland diseases, taking adequate techniques and recent technical developments into consideration. Data sources and study eligibility criteria: A systematic literature search was performed in Pubmed using various specific key words. Results: According to the literature results, including our own experiences, ultrasound is of value in up to >90% of cases presenting with inflammatory and/or obstructive diseases. Technical developments (e.g., elastography) and the application of modified ultrasound techniques (e.g., transoral ultrasound) have contributed to these results. Today, ultrasound is considered a first-line diagnostic tool in these diseases. However, in some inflammatory diseases, the final diagnosis can be made only after inclusion of the anamnesis, clinical symptoms, serologic blood tests, or histopathologic investiga-tion. Conclusions: Ultrasound can be considered as a first-line diagnostic tool in obstructive and inflammatory salivary gland diseases. In obstructive diseases, it may be sufficient for diagnostics in >90% of cases. In inflammatory diseases, ultrasound is at least an excellent screening method and can be used to establish the diagnosis in cases of an early suspicion. In all diseases ultrasound can contribute to better management and can be used for monitoring during follow-up.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Inflammatory; Obstructive; Salivary calculi; Salivary gland; Salivary gland diagnosis; Salivary gland disorders; Salivary ultrasonography; Sialadenitis

Ultrasound in the Assessment of Parotid Duct Stenosis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Journal of Ultrasound in Medicine, 2019)
Objectives Parotid duct stenosis may occur with or without accompanying ductal anomalies, with associated differences in their pathogenesis and management. By identifying the characteristics of a stenosis, ultrasound (US) can assist in tailored management of parotid duct stenosis. The objective of this study was therefore to describe the US characteristics of parotid duct stenoses and to evaluate criteria for whether and in what ways these can be distinguished from each other by using US. Methods A total of 108 patients who presented with parotid duct stenoses (130 parotid glands) were examined with high-resolution US between 2014 and 2017. The stenoses were assessed for duct dilatation, location, signs of ductal anomalies (circular encroachments/webs, duct bending/kinking, and presence of a megaduct) and the echogenicity of the gland parenchyma. Results Ultrasound was able to distinguish between stenoses associated with ductal anomalies and those without anomalies. Webs (82.5% versus 7.8%; P < .001), kinking (75.0% versus 3.3%; P < .001), and a megaduct (87.50% versus 15.63%; P < .001) and a tendency toward normal echogenicity in the gland parenchyma (77.5% versus 25.6%; P < .001) were significantly associated with ductal anomalies. Stenoses associated with ductal anomalies also had significantly larger duct diameters in comparison with those without anomalies (mean +/- SD, 9.19 +/- 3.65 versus 3.27 +/- 2.17 mm; P < .001). Conclusions This study describes US parameters that allow more detailed characterization of parotid stenoses with or without accompanying ductal anomalies. Differentiating between these at an early stage may be helpful for decision making on the further management in these patients.
CRIS-Team WoS Importer:2019-11-01

Ultrasound in the diagnosis of parotid duct obstruction not caused by sialolithiasis: diagnostic value in reference to direct visualization with sialendoscopy - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Dentomaxillofacial Radiology, 2021)
Objectives: The aim of this study was to evaluate the diagnostic value of ultrasound in the obstructive pathology of the parotic gland not caused by sialolithiasis using sialendoscopy as reference standard.
CRIS-Team WoS Importer:2021-03-26

Ultrasound Supplemented by Sialendoscopy: Diagnostic Value in Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Otolaryngology-Head and Neck Surgery, 2018)
Objective To assess the value of ultrasound, if indicated, supplemented by sialendoscopy, in the diagnosis of sialolithiasis. Study Design Retrospective study. Setting Referring center for salivary gland diseases. Subjects and Methods All patients who presented with a suspected diagnosis of obstructive sialopathy between January 2011 and April 2017 and had not undergone any treatment were retrospectively evaluated. A total of 2052 patients and 2277 glands were included in the study. Ultrasound examinations were carried out initially and followed by sialendoscopy in all cases. Direct demonstration of sialothiasis by sialendoscopy, transoral ductal surgery, and discharge of concrements/observation of fragments during sialendoscopy after extracorporeal shock-wave lithotripsy were regarded as definitive evidence of sialolithiasis. Results Ultrasound had an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 94.77%, 94.91%, 94.57%, 96.14%, and 92.89%, respectively, for the diagnosis of sialolithiasis. All false-positive findings were correctly diagnosed, and in all false-negative findings, stones/fragments were visualized by sialendoscopy. Over 95% of the false-negative findings in major salivary glands (64/67) had visible ductal dilation in sonography, and in 73.1%, the stones not detected on ultrasound were located in the distal part of the duct, which is easily accessible with the sialendoscope. Conclusion This study shows that sialolithiasis can be diagnosed using ultrasonography with a high degree of certainty. If supplemented by sialendoscopy, the correct diagnosis could be established in virtually all cases of sialolithiasis. Ultrasound supplemented by sialendoscopy has the potential to serve as an alternative diagnostic standard in the future.
EVALuna2:35387

Value of Sonography in the Diagnosis of Sialolithiasis: Comparison With the Reference Standard of Direct Stone Identification - Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich; Wüst, Wolfgang; Mantsopoulos, Konstantinos; Koch, Michael (Journal of Ultrasound in Medicine, 2017)
The aim of this study was to assess the effectiveness of sonography for diagnosing sialolithiasis in comparison with the existing reference standard of direct identification of a stone.A total of 659 glands with signs of obstructive sialadenopathy were evaluated retrospectively. Sonographic examinations of the large head salivary glands had been performed initially in all cases. Direct depiction of a stone during sialoendoscopy or transoral ductal surgery or observation of stone fragmentation with discharge of concrements after extracorporeal shock wave lithotripsy, was regarded as definitive evidence and as the reference standard for the presence of sialolithiasis. The sonographic results were compared with those for direct identification of stones.The sensitivity of sonography was 94.7%, with specificity of 97.4%, a positive predictive value of 99.4%, and a negative predictive value of 79.6%. Stones that were not diagnosed correctly on sonography were most often located in the distal area of the duct.These results show that sialolithiasis can be diagnosed by sonography with a high degree of certainty. Sonography thus appears to be highly appropriate as the examination method of choice.
EVALuna2:14673